2019
DOI: 10.1002/ecs2.2636
|View full text |Cite
|
Sign up to set email alerts
|

Observations of a novel predatory gull behavior on an invasive ascidian: A new consequence of coastal urban sprawl?

Abstract: Coastal urbanization has a dramatic effect on both terrestrial and marine ecosystems, altering resources such as food or space. Many species have shifted their ranges in response to anthropogenic pressures, resulting in novel species interactions. Here, we report an observation of a novel foraging behavior of the European Herring Gull (Larus argentatus): the capture and consumption of the widespread sea squirt Ciona intestinalis from under floating pontoons in a recreational marina in Ireland. Multiple gulls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In addition, this smashing method is known for a long time (Oldham, 1930) and occurs worldwide (Cadée, 2001). Moreover, it is worth to note that observation of gulls feeding on NIS species has been already recorded in the literature (Cadée, 2000(Cadée, , 2001(Cadée, , 2008Holman et al, 2019). For instance, Cadée (2000Cadée ( , 2001Cadée ( , 2008 reported herring gulls carrying the NIS Pacific oysters (C. gigas) or the NIS E. directus to high altitude and drop them onto rocks to crack them open and to feed them.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In addition, this smashing method is known for a long time (Oldham, 1930) and occurs worldwide (Cadée, 2001). Moreover, it is worth to note that observation of gulls feeding on NIS species has been already recorded in the literature (Cadée, 2000(Cadée, , 2001(Cadée, , 2008Holman et al, 2019). For instance, Cadée (2000Cadée ( , 2001Cadée ( , 2008 reported herring gulls carrying the NIS Pacific oysters (C. gigas) or the NIS E. directus to high altitude and drop them onto rocks to crack them open and to feed them.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, Cadée (2000, 2001, 2008) reported herring gulls carrying the NIS Pacific oysters ( C. gigas ) or the NIS E. directus to high altitude and drop them onto rocks to crack them open and to feed them. Similarly, in 2018, Holman et al (2019) observed a new behavior of herring gull feeding on C. intestinalis in a recreational marina in Ireland. In this study, the authors observed a gull diving down below the pontoons and emerging with a sea squirt of the non‐native species C. intestinalis .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation